The 3‐day bladder diary is a feasible, reliable and valid tool to evaluate the lower urinary tract symptoms in women. Issue 2 (22nd November 2013) - Jimenez‐Cidre, Miguel A.; Lopez‐Fando, Luis; Esteban‐Fuertes, Manuel; Prieto‐Chaparro, Luis; Llorens‐Martinez, Francisco J.; Salinas‐Casado, Jesus; Castro‐Diaz, David; Müller‐Arteaga, Carlos; Adot‐Zurbano, Jose M.; Rodriguez‐Escobar, Fernando; Gutierrez, Cristina; Arlandis‐Guzman, Salvador; et al.
<x xml:space="preserve">Abstract</x> Aims To evaluate the feasibility (% of completion), reliability (test–retest and inter‐observer) and validity (convergent vs. questionnaires and vs. urodynamic study‐UDS) of the 3‐day bladder diary (3dBD) in women with lower urinary tract symptoms (LUTS). Methods Epidemiological, descriptive, cross‐sectional and prospective study. Fourteen Functional Urology and Urodynamic Units participated. One hundred thirty‐six women with mean age (SD) 55.2 (13.8) years with LUTS, without bladder catheterization and who were able to fill in the 3dBD were included. An UDS was performed. They filled in the 3dBD in two times separated by 15 days (test and retest), the International Consultation on Incontinence—Short Form (ICIQ‐UI SF) and the Bladder Control Self‐Assessment Questionnaire (BSAQ). Results One hundred ten women completed 3dBD for test and retest. Feasibility: each 3dBD has 42 variables, 77.2% women completed 80%. Test–retest reliability: there were not differences in the proportion of patients classified as positive for each symptom (urgency: P = 0.3173; incontinence: P = 1; nocturia: P = 0.0522; frequency: P = 0.4386). The Intraclass Correlation Coefficient (ICC) ranged from 0.67 to 0.92, except for night time VVmax which was lower (0.54). Inter‐observer reliability: ICC ranged from 0.64 to 0.99, except for day time VVmax (0.29) and the number of urgency episodes (0.45). Validity: Spearman correlation coefficients for ICIQ‐UI SF and BSAQ ranged from 0.4 to 0.6 (P < 0.0001) and for UDS were lower (P < 0.05). Conclusions The 3dBD showed good feasibility, reliability and validity to be used in the assessment of LUTS in women. Neurourol. Urodynam. 34:128–132, 2015. © 2013 Wiley Periodicals, Inc.